Altered white matter in cocaine-dependent subjects with traumatic brain injury: A diffusion tensor imaging study. (1st June 2015) - Ma, Liangsuo; Steinberg, Joel L.; Keyser-Marcus, Lori; Ramesh, Divya; Narayana, Ponnada A.; Merchant, Randall E.; Moeller, F. Gerard; Cifu, David X.
Highlights: We tested white matter impairment in cocaine-dependent subjects (CDs). We conducted diffusion tensor imaging Tract-Based Spatial Statistics (TBSS) analysis. CDs with mild traumatic brain injury (mTBI), CDs without mTBI, and controls were compared. CDs with mTBI had lower fractional anisotropy (FA) on corpus callosum (CC) than controls. The concurrence of cocaine dependence and mTBI might result in more severe damage to the CC. Abstract: Background: Diffusion tensor imaging (DTI) is a useful technique for non-invasively investigating the microstructural organization of white matter (WM), and the most consistent DTI finding regarding cocaine-related WM alterations is in the corpus callosum (CC). WM injury has also been observed in subjects with traumatic brain injury (TBI), including in the CC. Methods: We used DTI to test if the WM microstructure is relatively more impaired in cocaine-dependent subjects who had suffered a mild TBI (mTBI). Fractional anisotropy (FA), which reflects the degree of alignment of cellular structures within fiber tracts and their structural integrity, was compared across cocaine-dependent subjects with mTBI (COCTBI group, n = 9), matched cocaine-dependent subjects without TBI (COC group, n = 12), and matched healthy controls (CTL group, n = 12). Results: The COCTBI group had significantly lower FA in the genu, body, and splenium of CC, than the CTL group whenever the education was controlled or not. The COC group had significantly lower FA in the left and right anterior corona radiata than the CTL group only when the education was controlled. There was no significant difference in FA between the COC and COCTBI groups. Conclusion: Cocaine dependence (or mTBI) related WM impairments in the CC were not detectable in this small subject sample. The significant finding in the CC suggests that the concurrence of cocaine dependence and mTBI might result in more severe damage to the CC, which could even be detected in small sample size.